Consumer Perception of Product Quality, Price, Brand and Celebrity Endorser in Making Decisions to Purchase “EsTeh Indonesia” - Rima Shobiroh; Nuriah Yuliati; Eko Nurhadi (Cita konsultindo, 2024)
This research investigates how Indonesian consumers decide to purchase EsTeh Indonesia beverages. It focuses on four factors: product quality, price, brand image, and the influence of celebrity endorsements. The study employs a combination of descriptive analysis and Structural Equation Modeling (SEM) to understand how these factors relate to buying decisions. The results reveal that consumers prefer to buy EsTeh Indonesia at physical outlets due to the inviting atmosphere and convenience. More importantly, the study finds that both product quality and price significantly influence purchasing decisions. Brand image also has a positive impact, but interestingly, celebrity endorsements have no significant effect. Overall, the research model demonstrates a good fit and provides strong evidence for the importance of product quality and price in driving consumer choices. This offers valuable insights for EsTeh Indonesia to strengthen its market position and build a loyal customer base by focusing on these key factors.